GERMAN LEGAL TERMINOLOGY IN THE AREA OF HIGHER EDUCATION AND THE USE OF ENGLISH IN THE NATIONAL VARIETIES OF GERMAN SPOKEN IN AUSTRIA, GERMANY AND SWITZERLAND - WISSIK, Tanja (Comparative Legilinguistics, 2017)
This paper investigates German legal terminology in the area of higher education in Austria, Germany and Switzerland. Particular emphasis is put on the influence of English in this field arising from internationalization and the creation of the European Higher Education Area. One can assume that due to the Bologna Process – initiated on the European level with the aim of creating more comparable, compatible and coherent higher education systems – there is a wider use of English terminology than before in the field of higher education. German legal and administrative language employed in the higher education sector in the aforementioned countries has been analysed within the framework of this study with the help of comparable specialized corpora of university legislative texts. In addition, a reference corpus of international legal texts dealing with the same topic has been employed. The analysis will endeavour to establish to what extent English terminology is being used.